2012
DOI: 10.1017/s1755773912000264
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Europarties on Central and Eastern European partner parties: a theoretical and analytical model

Abstract: This article provides a comprehensive theoretical model for analysing the influence of European party federations (Europarties) on their Central and Eastern European (CEE) partner parties. It draws on the concepts of Europeanization and party change and is, in principle, applicable to similar processes of party enlargement elsewhere. In the process of their Eastern enlargement, Europarties have searched for suitable CEE partner parties on which they have tried to exert influence. Thus far, little is known abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Our findings also have important implications for the literature on the influence of European party groups and federations on national partner parties in CEE countries. In line with scholarship on Europeanization (Schimmelfennig and Sedelmeier, ), this literature assumed that European party groups were able to ‘Westeuropeanize’ CEE parties by the exchange of material and immaterial resources as well as through socialization processes (Delsoldato, ; Lewis and Mansfeldová, ; von dem Berge and Poguntke, ). Today we see that European party groups have been reluctant to enforce adherence to liberal democratic norms as they are incentivized to maximize their number of seats in the EP – the suspension of the Slovak Direction‐Social Democracy (SMER‐SD) by the Progressive Alliance of Socialists and Democrats (PES/S&D) is an exception to this rule (Haughton, ).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Our findings also have important implications for the literature on the influence of European party groups and federations on national partner parties in CEE countries. In line with scholarship on Europeanization (Schimmelfennig and Sedelmeier, ), this literature assumed that European party groups were able to ‘Westeuropeanize’ CEE parties by the exchange of material and immaterial resources as well as through socialization processes (Delsoldato, ; Lewis and Mansfeldová, ; von dem Berge and Poguntke, ). Today we see that European party groups have been reluctant to enforce adherence to liberal democratic norms as they are incentivized to maximize their number of seats in the EP – the suspension of the Slovak Direction‐Social Democracy (SMER‐SD) by the Progressive Alliance of Socialists and Democrats (PES/S&D) is an exception to this rule (Haughton, ).…”
Section: Resultsmentioning
confidence: 94%
“…Today we see that European party groups have been reluctant to enforce adherence to liberal democratic norms as they are incentivized to maximize their number of seats in the EP – the suspension of the Slovak Direction‐Social Democracy (SMER‐SD) by the Progressive Alliance of Socialists and Democrats (PES/S&D) is an exception to this rule (Haughton, ). In the case of Fidesz and the EPP it seems that the size of Fidesz in the EP and as a a player in the Council has led the EPP to ‘accept a difficult, that is, not very compatible, partner among its ranks’ (von dem Berge and Poguntke, , p. 320).…”
Section: Resultsmentioning
confidence: 99%
“…A good way of illustrating this phenomenon is examining the role of transnational party actors (TPA). Many scholars suggested that TPA played a significant role during the accession process, especially in the states Vachudova saw as ‘illiberal’ (for example, Pridham, ; Spirova, ), not least offering to those parties linked to TPAs ‘financial and material resources, expertise and legitimacy’ (Von dem Berge and Poguntke, , p. 312). Even those who suggest a more limited impact see TPA as playing the role of a ‘badge of approval’ or kite mark (Haughton and Rybář, ).…”
Section: Boundaries: On the Margins But Not Necessarily Marginalmentioning
confidence: 99%
“…The rationalist external incentives and constructivist socialisation models of Europeanisation (Schimmelfennig and Sedelmeier, 2005;Sedelmier, 2011;Vachudova, 2005;von dem Berge and Poguntke, 2013) suggest the mechanisms through the Europarties might be able to influence electoral coalitions and mergers in Central and Eastern Europe. The external incentives model, building on the "logic of consequences" (Hall and Taylor, 1996), posits that the Europarty provides various resources to CEE parties in exchange for them following the recommendations of the Europarty on on cooperating with some parties but not others.…”
Section: Mechanisms Of Europarties' Influence: External Incentives Modelmentioning
confidence: 99%